Mesothelin-specific CAR-T cell therapy that incorporates an HLA-gated safety mechanism selectively kills tumor cells. Issue 1 (28th January 2022) - Tokatlian, Talar; Asuelime, Grace E; Mock, Jee-Young; DiAndreth, Breanna; Sharma, Shruti; Toledo Warshaviak, Dora; Daris, Mark E; Bolanos, Kristian; Luna, Breanna L; Naradikian, Martin S; Deshmukh, Kiran; Hamburger, Agnes E; et al.
Abstract : Background: Mesothelin (MSLN) is a classic tumor-associated antigen that is expressed in lung cancer and many other solid tumors. However, MSLN is also expressed in normal mesothelium which creates a significant risk of serious inflammation for MSLN-directed therapeutics. We have developed a dual-receptor (Tmod™) system that exploits the difference between tumor and normal tissue in a subset of patients with defined heterozygous gene loss (LOH) in their tumors. Methods: T cells engineered with the MSLN CAR Tmod construct described here contain (1) a novel MSLN-activated CAR and (2) an HLA-A*02-gated inhibitory receptor (blocker). A*02 binding is intended to override T-cell cytotoxicity, even in the presence of MSLN. The Tmod system is designed to treat heterozygous HLA class I patients, selected for HLA LOH. When A*02 is absent from tumors selected for LOH, the MSLN Tmod cells are predicted to mediate potent killing of the MSLN(+)A*02(−) malignant cells. Results: The sensitivity of the MSLN Tmod cells is comparable with a benchmark MSLN CAR-T that was active but toxic in the clinic. Unlike MSLN CAR-T cells, the Tmod system robustly protects surrogate "normal" cells even in mixed-cell populations in vitro and in a xenograft model. The MSLN CAR can also be paired with other HLA class I blockers, supporting extension of the approach to patients beyond A*02 heterozygotes. Conclusions: The Tmod mechanism exemplified by the MSLN CAR Tmod construct provides an alternative route to leverage solid-tumor antigens such as MSLN in safer, more effective ways than previously possible.